Pelatihan English for Tourism Berbasis Sumber Daya dan Kearifan Lokal bagi Pelaku Wisata di Timbanuh, Kabupaten Lombok Timur - Wardana, Lalu Ali; Sahrul; Suryaningsih, Hartati; Shallaita, Baiq Annisa; Tsaqiila, Thalia Qaulan (Universitas Mataram, 2025)
This Community Service Program (PKM) aims at enhancing the English communication skills of tourism practitioners in Timbanuh Village, Pringgasela, East Lombok. The urgency lies in the need for local tourism practitioners to adapt to the global market, which emphasizes sustainability and the competitiveness of local destinations. The PKM also serves to expand productive and inclusive employment opportunities while supporting the village's economic sustainability through more professional tourism management. The PKM was designed as English for Tourism training based on local resources and wisdom. The training was conducted in four phases: vocabulary and phrases, expressions related to English for Tourism, interactive exercises, and intercultural learning. The activities were delivered through a learning model that integrates theory and practice, alongside interactive discussions. The results of this PKM indicate an improvement in participants’ English proficiency within the context of tourism.